Isolation And Characterization of Trichoderma Sp. And Its Antagonism Activity Against Fusarium Wilt In Shallots - La Mudi; Zainal Abidin; Ida Maratul Hamidah; Helmi Ahmad Gyn’nandi; Rusmini Rusmini; Riama Rita Manullang; Andi Lisnawati; Gusti Ayu Kade Sutariati (International Journal of Science and Environment (IJSE), 2025)
Moler disease in shallots, particularly during the rainy season, caused a significant decline in production. As a solution, biological control using indigenous Trichoderma sp. was needed, as it functioned both as a biocontrol agent and a plant growth promoter. This study aimed to isolate and characterize Trichoderma sp. from the BTP Study Program Pilot Garden and to evaluate its antagonistic potential against moler disease in vitro. The research was conducted at the Agronomy Laboratory of Samarinda State Agricultural Polytechnic from July to August 2024. Observed variables included macroscopic and microscopic characteristics, as well as inhibition tests. Characterization data were analyzed descriptively, while inhibition test results were analyzed using analysis of variance (ANOVA), followed by a P-value of 0.05. Based on the isolation results, four isolates of Trichoderma sp. were isolated from the vegetation of palm oil plants, rubber plants, and pepper plants, exhibiting morphologically and microscopically distinct characteristics. Based on the morphological and microscopic characters, the TP2 isolate was suspected to be Trichoderma sp., the TH2 isolate was identified as T. hamatum, the TE1 isolate was assumed to be T. harzianum, and the TE2 isolate was thought to be T. koningi. The results of the antagonist test showed that the Trichoderma sp. isolates could act as biological controllers, as shown by the inhibition test results ranging from 35.16% to 69.46%. These findings indicated that the indigenous Trichoderma isolates had promising potential as biological control agents and could be further developed for field application to manage moler disease in shallots effectively.